Maqashid Shariah-Based Assessment of CWLS SW001 in Enhancing Productive Waqf - Hasibuan, Abdul Razak; Achiria, Siti; Saeidi, Hadi (Takaza Innovatix Labs Ltd., 2025)
This study examines the implementation of CWLS SW001, a cash waqf-linked sukuk instrument managed through private placement by the Indonesia Waqf Board (BWI). Acting as the sole wakif representative for individuals and institutions, funds collected via sukuk are allocated to productive projects, such as building the Retina and Glaucoma Center at RS Mata Achmad Wardi, Serang, Banten, and providing free healthcare services for 2,513 patients. The analysis reveals that CWLS SW001 aligns with the principles of Maqashid Syariah, addressing hajjiyat-level needs that enhance social welfare and economic inclusivity without compromising the five core objectives of Shariah: religion, life, intellect, lineage, and wealth. This platform not only integrates Islamic values with modern financial instruments but also demonstrates how waqf can serve as a sustainable funding source for public health infrastructure. Recommendations for stakeholders include increasing public awareness and adopting alternative issuance mechanisms to empower wakif in deciding the allocation of funds. This study highlights the potential of CWLS as a transformative tool for waqf management and invites further exploration into its regulatory and operational frameworks to maximize its societal benefits.